Social Characteristics of Squid Fishermen Conditions in Improving Household Welfare and Income, Lampung - Riantini, Maya; Bidarti, Agustina; Bursan, Rinaldi; Listiana, Indah; Al Faris, Luthfi Naufal (Journal of Tropical Marine Science, 2023)
The level of income determines the welfare of fishermen. The aim of this study was to determine the relationship between the income level of squid fishermen and household incomse with the condition of squid fishermen. This study was conducted in Sukajaya Lempasing Village, Teluk Pandan District, Pesawaran Regency, Lampung. The results of the study showed that squid fisherman households with income above the minimum wage (prosperous) value have side jobs that can increase their income to meet the daily needs. The welfare level of squid fishermen is in the poor to moderate category. Education is a human right for every Indonesian citizen, thus every citizen has the right to get a proper education. Education is an important indicator in measuring household welfare. The difference in the education level will certainly affect the level of welfare obtained by each household. Most of the squid fishermen are in a prosperous condition because they have high scores on every welfare indicator, especially on education indicators, consumption levels and patterns as well as housing and environmental indicators.